The Battle of Qattan and its political repercussions on the Khutta and Seljuk state In the Abbasid era in the year 536 AH / 1141 AD (Journal of the College of Basic Education, 2023)
The study of the Turkish tribes and their relations with their neighbors and contemporary powers is one of the most importantHistorical studies through different historical stages, despite the scarcity of sources that dealt withA study of these tribes and their rarity, and the Al-Khatta tribe or the “Qarkha’ites” (1) are among the most important tribes that have not beenshed light on it and the important role it played throughout the historical stages, politically and militarily.The aspirations of the kings of the wrong state had a great impact in changing the course of several historical events, includingWhile they were engaged in several battles with their competitors, led by the Seljuks, who were representingThe first danger in front of them, and for this reason the kings of error tried to confront the Seljuks and put an end to them.